1992
DOI: 10.2165/00003088-199222010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Amlodipine

Abstract: Amlodipine is a dihydropyridine calcium antagonist drug with distinctive pharmacokinetic characteristics which appear to be attributable to a high degree of ionisation. Following oral administration, bioavailability is 60 to 65% and plasma concentrations rise gradually to peak 6 to 8h after administration. Amlodipine is extensively metabolised in the liver (but there is no significant presystemic or first-pass metabolism) and is slowly cleared with a terminal elimination half-life of 40 to 50h. Volume of distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
136
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(146 citation statements)
references
References 18 publications
9
136
0
1
Order By: Relevance
“…It has a half-life of 38 to 50 hours and full 24-hour duration of action that maintains a trough:peak ratio of 57.7, even 72 hours following abrupt withdrawal. 15,16 Combining amlodipine with any other agent, including benazepril, easily carries the BP-lowering effect throughout the 24-hour period. With these characteristics in mind, it is surprising that the differences in BP reduction were not greater in favor of the amlodipine-benazepril combination than those actually observed in ACCOMPLISH.…”
mentioning
confidence: 99%
“…It has a half-life of 38 to 50 hours and full 24-hour duration of action that maintains a trough:peak ratio of 57.7, even 72 hours following abrupt withdrawal. 15,16 Combining amlodipine with any other agent, including benazepril, easily carries the BP-lowering effect throughout the 24-hour period. With these characteristics in mind, it is surprising that the differences in BP reduction were not greater in favor of the amlodipine-benazepril combination than those actually observed in ACCOMPLISH.…”
mentioning
confidence: 99%
“…These changes were not significantly different from the corresponding observed in Group A was dependent upon pre-existing ACE inhibition. A potential pharmacokinetic effects of placebo (−0.7 and −1.8 mm Hg), whereas the changes with 4, 8 or 16 mg/day were greater than explanation is that amlodipine, which has a high affinity for protein, 21 might have displaced perindowith placebo. In this study, 6-h post-dose measurements were also made, and again showed changes prilat by non-specific binding to ACE.…”
Section: Resultsmentioning
confidence: 89%
“…Amlodipine is rapidly absorbed and is extensively metabolized in the liver while it shows linear dose-related pharmacokinetic characteristics and, at steadystate, there are relatively small fl uctuations in plasma concentrations across a dosage interval (Abernethy, 1992). Although structurally related to other dihydropyridine derivatives, amlodipine displays signifi cantly different pharmacokinetic characteristics (Meredith et al, 1992). Amlodipine is a substrate of cytochrome P450 (CYP) 3A subfamily, specifi cally CYP3A4 (Nishio et al, 2005;Kim et al, 2009).…”
Section: Introductionmentioning
confidence: 99%